Burden of Carbapenem Resistant Urinary Isolates of E. coli and Klebsiella at Tertiary Care Hospital - Sharma, Prerna; Sarwat, Tarana; Mahajan, Supriya; K Kakru, Dalip; Kaushik, Nidhi (Journal of Neonatal Surgery, 2025)
Background: Urinary tract infections are a significant cause of morbidity worldwide, with Escherichia coli and Klebsiella spp. Being the predominant causative agents. The emergence of carbapenem-resistant Enterobacteriaceae (CRE) poses a grave public health threat due to limited treatment options. Methods: A cross-sectional study was conducted from October 2023 to September 2024 in the Department of Microbiology at Sharda University. Urine samples from suspected UTI patients were processed using standard microbiological techniques. Isolates were identified using biochemical methods, and antimicrobial susceptibility testing was performed using the Kirby-Bauer disc diffusion method as per CLSI guidelines. Results: In the present study, out of 8154 urine samples, 1166 were culture positive, among which E. coli 712 (61.06%) and Klebsiella spp. 128 (10.97%) were the predominant isolates. Of these, 190 (26.68%) of E. coli and 54 (42.18% ) of Klebsiella species exhibited resistance to carbapenems. Conclusion: The increasing burden of carbapenem resistance in urinary pathogens underscores the need for antimicrobial stewardship, rapid diagnostic tools, and infection control practices in healthcare settings.